Analyze of Dramaturgy to Self Concept of Pupil TMI Al-Amien Prenduan (Erving Gofman’s Theory Analysis) - Nisak, Khoirun; Salimah, Ifa Dotus; Ma’ruf, Amar; Syaifuddin, Syaifuddin (Program Studi Tadris IPS Fakultas tarbiyah IAIN Kudus, 2022)
Human social life always be related with society interacting anywhere, anytime, and their lives present their selves as a theatre performers whose appearance can change at any time depending on the context. It happens in human life, whoever we are, and in any condition, we always interact in symbols. Maybe without us realizing it, it all happens in every